Approaching autonomous shuttle pilot programs in public transportation - Hunter, Alicia (Kansas State University, 2018)
Investment, research, and development of autonomous vehicles grows each year. As the years pass, more and more transit agencies are interested in incorporating autonomous vehicles as a public transit service. However, there are still unknowns and uncertainties as to the safety and viability of autonomous vehicles. For transit agencies to incorporate autonomous vehicles in public transit, agencies need to validate the application of autonomous vehicles in real-world scenarios and environments. One option for testing the vehicles is for transit agencies to implement an autonomous shuttle pilot program. A pilot program will give agencies an opportunity to learn if and how autonomous vehicles can enhance or improve transit services. Even though autonomous shuttle pilot programs have been deployed worldwide, there has been little comparative analysis. This report addresses the need for knowledge by providing practical considerations of essential pilot program elements. To assist transit agencies, this report illustrates previously executed autonomous shuttle pilot programs, identifies the core elements of a pilot program, and discusses the relationship between elements. To accomplish these tasks, this report reviews nine European autonomous shuttle pilot programs, literature surrounding the topic, and interviews key personnel associated with the pilot programs. The results of this research help transit agencies make informed decisions about approaching autonomous shuttle pilot programs in public transportation.
Keywords: Implementation; Recommendations; Transit agencies; Public transportation; Framework elementsAutonomous shuttle